2022
DOI: 10.2478/ethemes-2022-0008
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Digital Transformation of Insurance in the Republic of Serbia

Abstract: Implementation of IT innovations in insurance industry enhances actual business models and creates new ones. E-insurance refers to creating and providing insurance and connected financial services through digital solutions. In this paper the impact of IT usage and digitalization on insurance sector in the Republic of Serbia is analysed. The aim of the proposed analysis is to reveal the determinants of the adoption of innovative technological solutions in insurance in the Republic of Serbia. Relying on the TOE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(16 reference statements)
1
7
0
Order By: Relevance
“…However, this critical area, such as technology for bringing innovation to takaful products, is not found in the present literature (Qadri, Ali, Jafar, Tahir, & Abbasi, 2022). Hence, Tech Takaful is a new area that needs to be explored in the digital era's future model of the takaful sector (Stanković et al, 2022). Nevertheless, previous studies have discussed e-insurance acceptance at two levels: organisational and individual (Scupola, 2009).…”
Section: Literature Reviewmentioning
confidence: 81%
See 3 more Smart Citations
“…However, this critical area, such as technology for bringing innovation to takaful products, is not found in the present literature (Qadri, Ali, Jafar, Tahir, & Abbasi, 2022). Hence, Tech Takaful is a new area that needs to be explored in the digital era's future model of the takaful sector (Stanković et al, 2022). Nevertheless, previous studies have discussed e-insurance acceptance at two levels: organisational and individual (Scupola, 2009).…”
Section: Literature Reviewmentioning
confidence: 81%
“…The significant contribution of this research is the development of a new model for e-takaful, as fewer studies have been found on this topic compared to e-insurance. Hence, Tech Takaful needs to be explored in the digital era's future model of the takaful sector (Stanković et al, 2022). In addition, this study is essential to raise public awareness and help the government accomplish its goal of hastening the recovery from the COVID-19 pandemic, reducing poverty, fostering stability and prosperity, and encouraging "green economic growth" in the nation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Picture 1. The use of BDA in insurance product life cycle Many insurers start the transformation process by using BDA in certain activities of the products' lifecycle, for example, in marketing and sales (Stanković et al, 2022) insureds' everyday activities can be used to identify specific needs and to anticipate risks of certain insureds' segments. These information enables insurers to reveal the gaps between the current insurance coverage and insureds' requirements.…”
Section: The Use Of Big Data Analytics In the Insurance Product Lifec...mentioning
confidence: 99%